Is the hand to speech what speech is to the hand? - Mildner, Vesna (Array, 2000)
Interference between the manual and the verbal peformance on two types of concurrent verbal-manual tasks was studied on a sample of 48 female right-handers. The more complex verbal task (storytelling) affected both hands significantly, the less complex (essentially phonemic) task affected only the right hand, with insignificant negative influence on the left-hand performance. No significan reciprocal effects of the motor task on verbalization were found.